The Akuntabilitas Pengelolaan Alokasi Dana Desa Terhadap Kesejahteraan Finansial Masyarakat - Farhan Dama Rahadi (Yayasan Kawanad, 2023)
This research uses qualitative methods to evaluate accountability in the management of Village Fund Allocation (ADD) towards the financial welfare of the community in the Village of West Aceh Regency. This research aims to understand the extent to which community empowerment can be achieved using village funds. The approach used was descriptive qualitative involving 10 informants and data collection techniques including interviews, observation, and documentary studies. The research results show that good cooperation between the government and the community, community empowerment in participating in development programs, and transparency in the use of village funds are key factors in achieving development goals and community empowerment. The discussion underscores the importance of active community participation and accountability in managing village fund allocations to achieve sustainable village development. The policy implications identified include strengthening community participation mechanisms, increasing transparency and accountability in the management of village funds, as well as public education and advocacy to increase community awareness about the importance of empowerment and accountability in village development. The research conclusions emphasize the need to comply with established rules, apply strict village fund management principles, encourage active community participation, good administration, and ensure community institutions function in accordance with their duties and missions. It is hoped that these steps can increase the effectiveness of community empowerment through village fund allocation and have a positive impact on overall village development